PENINGKATAN KUALITAS JALAN PONDOK PESANTREN ‘AINUL HAYAH MELALUI PELATIHAN PEMBUATAN PAVING BLOCK - Lubis, Adina Sari; Harahap, Muthiah Putrilan Syamnah; Syarvina, Syarvina; Nasution, Derry Wiliyanda (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2026)
The internal road access at Ainul Hayah Islamic Boarding School in Deli Serdang remains unpaved, leading to slippery and muddy conditions during the rainy season and increasing safety risks for students and the surrounding community. Limited financial resources also constrain the implementation of conventional pavement solutions. This community service program aims to improve road quality through participatory training in the production and installation of paving blocks. The method employed a participatory and applicative approach, including preliminary surveys, hands-on training in manual paving block production, laboratory testing of compressive strength at 28 days, and field implementation of paving installation. The results show that participants were able to independently produce and install paving blocks, with compressive strength values generally ranging from quality D to approaching quality C based on SNI 03-0691-1996 standards. The installed pavement significantly improved road conditions, making them more stable, less muddy, and safer for daily use. In addition, the program enhanced participants’ technical skills, knowledge, and confidence, contributing to the community’s self-reliance in simple infrastructure development. This study demonstrates that participatory training combined with appropriate technology can effectively address infrastructure problems while empowering local communities, and it has strong potential for replication in similar educational and residential settings.